2010
DOI: 10.1159/000314266
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Affect Patients’ Decision-Making about Mastectomy or Breast Conserving Surgery, and the Psychological Effect of this Choice on Breast Cancer Patients

Abstract: Background: Breast cancer is the most common cancer in women. Primary treatment is surgery, with breast conserving surgery (BCS) being widely used for early-stage disease. Due to changes in body image, depressive symptoms can occur after surgery. Here, we evaluate factors that affect patients’ decision on surgery, and investigate differences in the level of depression after mastectomy or BCS in a population of Turkish patients. Patients and Methods: One hundred breast cancer patients who had undergone mastecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 23 publications
(53 reference statements)
1
39
1
Order By: Relevance
“…In patriarchal societies, it is known that family members, especially husbands, are highly influential in the decision phase. A study conducted in Turkey in 2010 showed that married women were likely to prefer BCS due to concerns of losing their spouse [15]. After 7 years, our study revealed that BCS preference is higher among single women than among married patients.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…In patriarchal societies, it is known that family members, especially husbands, are highly influential in the decision phase. A study conducted in Turkey in 2010 showed that married women were likely to prefer BCS due to concerns of losing their spouse [15]. After 7 years, our study revealed that BCS preference is higher among single women than among married patients.…”
Section: Resultsmentioning
confidence: 57%
“…A study from 2010 reported that patients considered mastectomy as being oncologically safer than BCS and thus mastectomy rates were higher than BCS rates [15]. Since then, experience with BCS has increased, multidisciplinary approaches have become standard of care, intraoperative surgical margin assessment techniques have developed, and in experienced and well-equipped centers local recurrence rates have decreased to almost 1% with BCS.…”
Section: Resultsmentioning
confidence: 99%
“…19 Similarly, obtaining second opinions has altered surgical treatment in breast cancer, as women visiting a second surgeon have been shown to be more likely to undergo breast conserving surgery vs radical mastectomy. 11 Younger surgeons (younger than 50 years) were 2.5 times more likely to use MIRP. Current urological training exposes younger trainees to more minimally invasive procedures and, therefore, younger surgeons are likely more inclined to offer MIRP vs RRP.…”
Section: Discussionmentioning
confidence: 96%
“…For example, patient age, parity and family history were significant determinants for undergoing breast conserving surgery vs mastectomy for breast cancer. 11 In addition, among patients undergoing anterior cruciate ligament reconstruction, those who conducted significant Internet based research or had higher levels of education were more likely to choose allografts vs autografts. 12 Surgeon level characteristics also contributed to variability in the selection of MIRP vs RRP, although to a lesser extent than patient level characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, emotions affect choice either positively or negatively (Baker, 2006;Burge & Street, 2010;Federman, Wisinversky, Wolf, Leventhal, & Halm, 2010;Goodwin, Zhang, & Ostir, 2004;Gumus et al, 2010;Gurland, & Gurland(a), 2009;Joon, Kim, Shanker, & Han, 2004;Matsuoka et al, 2011;Visser et al, 2009;Wang, Novemsky, Dhar, & Baumeister, 2010). Yet, the underpinnings of the relationship between choice and depressive symptoms arise from the interrelationship between choice, independence, and retirement, and therefore, these interrelationships require closer examination.…”
Section: The Relationship Between Choice and Depressive Symptomsmentioning
confidence: 99%